Cognitive-epistemological obstacles and explanatory models in the study on the structure of matters in physical classes - Márlon Pessanha (Investigações em Ensino de Ciências, 2018)
The knowledge involved in Modern and Contemporary Physics breaks not only with forms of thinking proper to common-sense knowledge, but also with forms of thinking typical of classical science. Thus, the discussion about their teaching and learning in High School goes through the understanding about how ways of thinking and building knowledge affects the elaboration of explanatory models. In this research, based on Bachelard's notions of rupture and epistemological obstacle, and in an approach to studies on mental and conceptual models, we seek to understand how cognitive-epistemological obstacles act in the construction of explanatory models about the structure of matter. For that, physics classes were recorded in two contexts, Catalan secondary education in Spain, and high school in São Paulo. From a qualitative and interpretive analysis it was possible to identify cognitive-epistemological obstacles related to the naive perception of everyday phenomena, using metaphors and images, and with a limited and incongruent reasoning. As we have seen, these obstacles made it difficult to construct mental models that approached the target conceptual model. We believe that the analyzes and conclusions presented in this paper contribute to a necessary discussion about the role of cognitive-epistemological obstacles in the learning of concepts involved in Modern and Contemporary Physics.